English learning motivation and pragmatic competence: Correlational study of non-English major postgraduate students in java - Hidayatullah, Muhammad Syahied; Hidayanto, Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research aims to investigate the significant relationship between English learning motivation and pragmatic competence of non-English major postgraduate students and their current pragmatic competence. 350 non-English major postgraduate students from Javanese provinces (West, Central, and East Java) participated in this study. This study was quantitative research in the form of a correlational study by using one adapted questionnaire (Attitude and Motivation Test Battery (AMTB)) for English learning motivation and two kinds of adapted pragmatic competence tests (Multiple-choice Discourse Completion Test (MDCT) and Written Discourse Completion Test (WDCT)). The data were analyzed by using Normality Test, Linearity Test, Bivariate Pearson Product Moment, and Descriptive statistical analysis by IBM SPSS 26. The finding indicated English learning motivation correlated with English pragmatic competence. Although the correlation degree was 0.563 which had a moderate degree of correlation, they have a positive correlation which means the English learning motivation has contributed to the pragmatic competence. The current level of the non-English major postgraduate students’ pragmatic competence in Javanese provinces was categorized as still developing because the students hardly understand responses in the pragmatic competence test, especially in pragmatic awareness.